THE EFFECT OF INSTANT MESSENGER USAGE TO INTERNAL COMMUNICATION (Study in The Ministry of Communication and Information Technology of Republic of Indonesia Directorate General of Resources and Equipment for Post and Information Technology) - Amaliah Hajah; Astrid Siahaya (Atma Jaya Indonesia Catholic University, Jakarta, 2017)
The research discussed about instant messenger usage for internal communication at The Ministry of Communication and Information Technology of Republic of Indonesia (MCIT of RI) Directorate General of Resources and Equipment for Post and Information Technology. The research purpose was to determine the effect of instant messenger usage to internal communication by using the quantitative method. The results showed that there is a significant and positive effect by the instant messenger usage to employee communications. It showed that instant messenger could accommodate employee communication, particularly for job-related formal communication. However, there are some information that do not convey through instant messenger, particularly the informal communication, such as regarding employee motivation, delivering the thoughts and feelings of employees, and the settlement of the conflict with fellow employees. Therefore, organization should encourage instant messenger usage in informal communication, relating to motivate employees through instant messenger, to create a good working relationship and increase employee relations.